A review on advancing clay-based geopolymers for high-temperature oil well cements: Mechanisms, durability, and applications - Money, Barima; Modather, Rayan Hassan; Abutu, David; Norasyikin, Ismail; Agi, Augustine Aja; Nyah, Francis; Siti Qurratu' Aini, Mahat (KeAi Publishing Communications Ltd., 2025)
Geopolymers are promising alternatives to Portland cement due to their lower carbon footprint, superior mechanical strength, durability, and reduced shrinkage. However, inconsistent data and significant variations in experimental results highlight the uncertainty surrounding the reaction mechanisms of clay-based geopolymers (CBGs) in high-temperature oil wells. This review provides critical insights into these mechanisms and summarizes CBG synthesis methods. It explores the reaction processes of CBGs under high-temperature oil well conditions and analyzes the variables influencing these mechanisms. This review also examines the application of CBGs in oil wells, focusing on the challenges and potential solutions. Laboratory studies show that Portland cement degrades at temperatures above 300 °F (150 °C), while CBGs maintain their integrity and strength at temperatures up to 1500 °F (815 °C). This makes them particularly suitable for high-temperature geothermal wells and high-pressure, high-temperature oil well cementing. The dominant reaction mechanisms of CBGs include chemical reactivity, dissolution, gelation, polymerization, and growth. These findings highlight the potential of CBGs in addressing the challenges of high-temperature oil wells, thereby paving the way for further research in this area.